2021
DOI: 10.3390/ijerph18115772
|View full text |Cite
|
Sign up to set email alerts
|

‘Difficult Conversations with Patients’—A Modified Group Objective Structured Clinical Experience for Medical Students

Abstract: This study presents a modified Group Objective Structured Clinical Experience (GOSCE) focused on difficult conversations, in which, due to limited time and financial resources, only some students could actively participate in scenarios. We aimed to evaluate the intervention, including differences between them and observers. The intervention was organized for sixth-year medical students at a Polish medical university. The study protocol assumed a pre-post analysis of students’ attitudes and self-efficacy of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Both observers and receivers noted that the experience of observing a physician giving a patient an unfavorable diagnosis had contributed to their positive self-assessment of their own communication skills. Other studies support the view that students' participation in the communication course as observers and as active participants leads to higher confidence [22]. Thus, one may conclude that these types of experiences in DBN are educationally valuable.…”
Section: Receivers and Observersmentioning
confidence: 72%
“…Both observers and receivers noted that the experience of observing a physician giving a patient an unfavorable diagnosis had contributed to their positive self-assessment of their own communication skills. Other studies support the view that students' participation in the communication course as observers and as active participants leads to higher confidence [22]. Thus, one may conclude that these types of experiences in DBN are educationally valuable.…”
Section: Receivers and Observersmentioning
confidence: 72%
“…Therefore, some students might have difficulties in understanding the simulation based OSCE process and test questions. It was reported that the awareness of the simulated situation made students feel slightly unreal, where only 77% of the students speaking to the simulated patients felt like a real doctor [ 39 ]. Moreover, performance anxiety in certain students and examination unfamiliarity in both students and evaluators, probably caused relatively low performance rates in certain domains [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the conducted study, it seems worrisome that according to the respondents, only 35.1% had an occasion to discuss their volunteering experiences with the medical personnel and 12.3% with academic teachers. Although 86.0% of the volunteers had an occasion to discuss their experiences with their peers, as our previous research experiences show, at least in Poland, students may place a larger value on feedback from their teachers than that from other students [ 54 ]. Therefore, it seems reasonable to recommend that the introduction of volunteering learning should be simultaneously followed by obligatory reflection sessions in the presence of a mentor (e.g., a medical teacher or staff member).…”
Section: Discussionmentioning
confidence: 99%